SKALA KARAKTER RELIGIUS SEBAGAI ALAT UKUR KARAKTER RELIGIUS BAGI SISWA SEKOLAH MENENGAH KEJURUAN - Arofah, Laelatul; Andrianie, Santy; Ariyanto, Restu Dwi (Universitas Nusantara PGRI Kediri, 2021)
A great nation is not determined by the natural wealth and technology possessed by a nation, but because of the strong character of the nation. Based on this statement, strengthening character education needs to be implemented to support the strengthening of the character of the nation's next generation. Based on a preliminary study conducted in vocational high schools, it is found that many students have low religious character. This is necessary to remember the importance of religious character as a balance to other characters. The final goal to be realized in this study is to develop an android application innovation to strengthen the religious character of Vocational High School students that can be accepted theoretically and practically so that it can be widely used in educational settings as one of the guidance media that aims to overcome the problem of religious character in student classes. The development model used in this study was adapted from the development research model of Borg & Gall (1983). Currently the research process is in stage 3, namely the initial development of the wrong product design, namely developing a scale instrument for religious character. The scale of religious character consists of 28 statement items whose development is based on the religious dimensions of Glock and Strak (1974), namely dimensional beliefs, dimensions of religious practice, dimensions of appreciation, and dimensions of loss and experience. In this article we will build on the validity and reliability of the statement items on the religious character scale. The validity results obtained were in the form of 24 statement items that were declared valid and the instruments were declared valid for use, as evidenced by the reliability value of 0.971 or in the very high category. Based on the results of the validity and reliability, the scale of religious character can be used to measure the religious character of vocational school students Keyword: religious character, validity, reliability